An Exploration of Instructional Materials through the Math Adventure Approach to Enhance Students’ Numeracy Literacy in Island Region - Chrismanto Purba; Rina Ananta Sumawardani Sitepu; Karten Halirat (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This study aims to explore the application of teaching materials with the Math Adventure approach to improving students' Numeracy Literacy skills in the Two-Variable Linear Equation System (SPLDV) material. The method used is a pre-experimental design with a one-group pre-test-post-test design, involving 33 eighth-grade students at SMP Negeri 2 Dobo. Data were collected through a Numeracy Literacy ability test. The results of the study showed a significant increase in students' Numeracy Literacy skills after the application of teaching materials that had been explored with the Math Adventure approach, with an average score increasing from 41.58 to 83.27 and an average N-Gain value of 0.70. A total of 51.62% of students reached the Very Advanced category and 48.38% in the Advanced category. The results of the paired sample t-test showed a significant difference between the pre-test and post-test (p < 0.05). Thus, the integration of exploration of teaching materials with the Math Adventure approach has proven effective in improving students' Numeracy.